The Iran-Contra Scandal (1985-1986) is a historical-political study - حسن, یاسین خالد; عبداهلل, هاوار كمال میرزا (Sulaimani Journal for Humanities, 2025)
The secret relationship between Iran and America is one of the most complex issues, which many of its secrets are yet to be revealed. The sensitivity of the issue and the involvement of the authorities of the two countries including Ayatollah Khomeini and Ronald Regan, besides Israel, make the issue to be the subject of interest even today. Iran was making attempts to save its Islamic regime and the mutual interests of America with Iran made the two countries come closer in that period. Besides that, the reveal of the relations was a tremendous scandal for both sides, particularly America. The article relies on a political and historical approach to academically clarify the relationship of Iran with America. It consists of an introduction and three arguments. The first argument addresses the relationship of Iran with America under the influence of Israel. The second argument discusses the transportation of weapons to Iran by America. The third argument draws attention to the scandal of Iran- Jantraw and its effects in the deterioration of the relations. The article finally concludes its arguments and briefly mentions its findings.